Aramid‐Al2O3 Nano‐Needle Scaffold as Pore Former for Optimal Mechanical and Permeable Properties of Ceramic Matrix. Issue 9 (4th July 2014) - Chen, Xinwei; Tan, Yirong; Hong, Liang; Colombo, P.
<x xml:space="preserve">Abstract</x> An adroit design of pore‐forming system is required to achieve a porous ceramic matrix with high permeability and adequate mechanical strength. This work developed a hybrid pore‐forming regime constructed in the green body (dense powder packing) of yttria stabilized zirconia (YSZ) through the condensation polymerization to form poly(p‐phenylene terephthalamide) (PPTA) chains and their in‐situ grafting with alumina nano‐needles with pendant–NH2 groups (Sasol®). A PPTA‐Sasol pore‐former scaffold was resulted and distributed uniformly in the green body. It was then subjected to calcination treatment in Ar, through which fibers and ribbons consisting of carbon and alumina needles were derived and penetrated throughout the partially sintered YSZ matrix as the final form of pore‐former. This work further investigates the impacts of the PPTA‐Sasol pore‐former, including the morphologies and loadings, on the Darcy's permeability, pore‐size distribution and flexural strength, displayed by the porous YSZ matrices ultimately attained. It is showed that the vital role of Sasol needles in the present pore‐forming regime lies in significant enhancement on mechanical strength accompanying an improved permeability contrary to the best result achieved without them.